Biological Phosphorus Removal in Sequencing Batch Reactor at Longer Anaerobic Operating Period - H. Seah, K; Isma M.I, Aida; M, Hazmin.; M. Choo, C (International Journal of Engineering and Technology, 2018)
Two lab scale sequencing batch reactors were operated to evaluate phosphorus removal at 12-hours cycle. Plastic media was used as packing media in SBR1 and SBR2, respectively. A 12-hours operation cycle of both SBRs consisted of six consecutive stages that include filling (2 min), anaerobic phase (120 min), aerobic phase (480 min), settling (120 min), draw (30 min) and idle (15 min) which a digital timer was used to control it. SBR 2 will undergo a total of 12 hrs operation cycle with longer anaerobic time (240 min) and shorter aerobic time (360 min). The scanning electron microscope (SEM) and energy diffusive x-ray (EDX) analyser were used to characterize the formation of biofilm formed. Performance of SBR in terms of Chemical Oxygen Demand (COD) removal was consistently greater than 90%, irrespective to the of changes in anaerobic operating period. The average removal efficiencies for COD and phosphate were recorded at 92.2% and 68.3%, respectively for SBR1, 90.2% and 80.9%, respectively for SBR2. A longer anaerobic period in SBR2 led to the formation of more compact sludge granules and higher settling rate. SEM analysis revealed that spherical and rod shaped were the dominant species of bacteria in the biofilm grown on the surface of the plastic media. This concluded that the activities of Phosphorus-Accumulating Organisms (PAOs) species were probably inhibited in the reactor.Â